The level of understanding of income zakat and its implementation among muslims in state of Perak - Yaacob, Mazlah; Fathil, Fathiah; Khalid, Nurul Khairiah; Fathil, Fauziah; Abdullah, Ahmad Fauzee (Journal of Critical Reviews (JCR), 2020)
Income zakat is an annual tax or payment imposed on certain amount of income generated from either fixed or non-fixed sources, generally known as al-Mal al-Mustafad. In Malaysia, this kind of payment or zakat was first made mandatory in 1997 by National Fatwa Council Malaysia. The fatwa or decision was then gazetted by all state governments in Malaysia except that of Perak. This research aims to identify the level of understanding among Muslim community in the state of Perak regarding income zakat and its relevant procedures particularly the calculation of zakat. It is imperative to explore this issue since many Muslims of present day fail to perform zakat income as they are not aware of the tax or payment that has been made incumbent on them. Furthermore, the study also sheds light on the people’s level of understanding of how the zakat payment is to be calculated or counted. The findings of this study are useful for relevant agencies in particular religious bodies, in finding ways and means to disseminate awareness to the Muslims of their responsibility to pay income zakat, which will result in an increase of zakat revenue that can be then utilized for the enhancement of the economy of Muslims in the country.